Myocarditis After Covid- 19 Disease and its Prophylaxis. (Eurasian Medical Research Periodical, 2023)
The article summarizes the treatment experience of 37 patients treated in the hospital during the coronavirus pandemic. Clinical manifestations, age, diagnostic methods are discussed and suggestions are given.